2008
DOI: 10.1097/bsd.0b013e318150d121
|View full text |Cite
|
Sign up to set email alerts
|

Motion Analysis of Bryan Cervical Disc Arthroplasty Versus Anterior Discectomy and Fusion: Results From a Prospective, Randomized, Multicenter, Clinical Trial

Abstract: The Bryan disc treatment, on average, maintained flexion/extension range of motion without degradation over 24 months. No ectopic bridging ossification was seen in any of the Bryan discs and no subsidence or displacement of the Bryan disc occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 21 publications
5
45
1
1
Order By: Relevance
“…Most authors [1-10, 12, 19] observed the effect of general motion preservation at the implanted level regardless of the specific prosthesis design. In those studies, some groups have shown an increased motion [1][2][3][4], whereas others have shown no change [5][6][7] or decreased motion [8][9][10]. In contrast to Du et al [4], CDR with the Discover disc was able to maintain a mean of 8.4 ± 6.3°of FSU ROM at the 2-year follow-up in our group, which was significantly less than the preoperative ROM (P = 0.008).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Most authors [1-10, 12, 19] observed the effect of general motion preservation at the implanted level regardless of the specific prosthesis design. In those studies, some groups have shown an increased motion [1][2][3][4], whereas others have shown no change [5][6][7] or decreased motion [8][9][10]. In contrast to Du et al [4], CDR with the Discover disc was able to maintain a mean of 8.4 ± 6.3°of FSU ROM at the 2-year follow-up in our group, which was significantly less than the preoperative ROM (P = 0.008).…”
Section: Discussioncontrasting
confidence: 52%
“…Currently, there are many commercially available artificial discs with different biomechanical properties. Some prostheses have shown increased ROM postoperatively [1][2][3][4], while others have shown no change [5][6][7] or decreased ROM [8][9][10]. Interestingly, some prostheses have been shown to aid in restoration of cervical lordosis postoperatively [11][12][13][14], while others have shown no change [2,4] or trend toward kyphosis [5,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, just four separate research groups have carried out sizeable RCTs of cervical disc arthroplasty vs fusion, although their results have been presented in multiple publications addressing different subtopics within the same trials or by individual groups of authors participating in the multicentre studies [3,25,29,37,38,[44][45][46]. Collectively, these and one other small RCT [42] have shown statistically superior or comparable results for arthroplasty in relation to patient-rated outcomes such as the Neck Disability Index (NDI), neck and arm pain and quality of life (SF36).…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these and one other small RCT [42] have shown statistically superior or comparable results for arthroplasty in relation to patient-rated outcomes such as the Neck Disability Index (NDI), neck and arm pain and quality of life (SF36). The maintenance of segmental mobility with disc arthroplasty, expected to contribute to a reduced development of adjacent level change, has also been documented in three trials [29,38,44]. Although these studies possess the acknowledged scientific rigour of RCTs, they are not without their limitations.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo kinematic studies using flexion/extension plain radiograms have also addressed the effects of anterior cervical fusion on the kinematics at the adjacent levels to fusion [4,8,[15][16][17][18][19][20][21][22]. Results of these studies were also variable.…”
Section: Introductionmentioning
confidence: 99%